Approaches of the patrimonialization process of the territory: Case of the Aypate archaeological site (2012-2016) - Morán-Jorquera, Jessica (2020)
A rich territory in natural resources, mainly water sources, in addition to a lush green that hides in its gut an Inca religious and administrative center. The province of Ayabaca in Piura is a place that despite its great natural and cultural wealth is characterized by poverty and lack of basic services. The present work includes an approach of the patrimonialization process that this territory has undergone, a process that threatens the subsistence economy of the communities and peasants. Likewise, some lights are presented on how this process could be improved through a participatory management.